SARS‐CoV‐2 omicron variant may present with severe sickle cell painful crisis: A report of two cases - Elrazi Ali (14777284) (2023)
Coronavirus disease 2019 (COVID-19) is a respiratory viral illness that is caused by coronavirus 2 (SARS-CoV-2). The disease often presents with non-specific symptoms such as fever, headache, and fatigue, accompanied by respiratory symptoms (e.g., cough and dyspnea) and other systemic involvement. Currently, the virus had shown significant changes and mutations that resulted in the emergence of different strains. Each strain varies in its virulence, disease severity, and the response of the body's immune system. Sickle cell disease characterized by hemolytic anemia particularly in associated with stress. Patients with sickle cell disease infected with SARS-CoV-2 are reported to have increased risk for hospitalization, thrombosis, and other complications compared with non-sickle cell patients. The Omicron variant causes mild disease in general population; however, in patients with sickle cell disease, the data are limited. We present two patients known to have sickle cell disease presented with a severe acute painful crisis that required hospitalization after infection with Omicron variant of the SARS-CoV-2 virus.  Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5934